(untitled) (Research, Society and Development, 2020)
The objective was to characterize a physical-chemical quality in soybeans. Storage units stored in municipalities in the Midwest region of Brazil. The soybeans were collected in eight grain storage units distributed in different municipalities in the Midwest region. It carried out a characterization of grains by means of moisture content, electrical conductivity, color, bulk density, mass of a thousand grains, pH, close composition and the acidity, peroxide and iodine indices of the oil. A physical characterization is shown with 127.15 µS cm-1 g-1 for electrical conductivity, 7.50 for pH, 55.74 for L *, 10.41 a * and 31.46 for b *, 33, 15 for chroma and 71.70 for h*, 163.91 g of corn mass and 701.00 kg m-3 of apparent specific mass. The proximal composition gave average values of 11.30% for moisture content, 32.11% for protein, 7.76% for fiber, 4.68% for ash, 20.62% for carbohydrates and 23.62% for the moisture content. oil. A characterization of the oil quality indexes shown with values of 0.08 mg KOH of oil-1 for acidity, 1.18 meq of O2 kg of oil-1 for peroxide, 30.72 g of I2 100 g of oil-1 for iodine. It concluded that the soybean grains of the municipalities of the Midwest region, regarding the physical and chemical quality of the grains, is within the quality standard according to the legislation and researched literature and the quality of the oil with the exception of iodine with values below the standard, is in the range that guarantees its quality.